ナンキョクイキ カイヨウ ケンキュウ ニ オケル フクゴウ リョウイキ ケンキュウ リツアン ニ カンスル ケンキュウ ショウシュウカイ ホウコク - 小達, 恒夫; オダテ, ツネオ; 工藤, 栄; クドウ, サカエ; 福地, 光男; フクチ, ミツオ; Odate, Tsuneo; Kudoh, Sakae; Fukuchi, Mitsuo (2002)
P(論文) 「南極域海洋研究における複合領域研究立案に関する研究小集会」を, 平成13年5月19日~21日の期間, 国立極地研究所大石研修施設において開催した。参加者は20名であった。本年度出発する第43次日本南極地域観測隊(The 43rd Japanese Antarctic Research Expedition, JARE-43)において, 「しらせ」以外の「専用観測船」による海洋観測計画が認められた。これは40年以上に渡る日本南極地域観測史上初めてのことである。JARE-43の「専用観測船」による観測計画は, 2001年11月~12月に実施されるオーストラリア南極観測隊の「オーロラ・オーストラリス号」の航海, 2002年1月に実施される東京大学海洋研究所「白鳳丸」の航海に続くもので, 対象海域での時系列データを取得する上でまたとない機会である。なお, 同海域には3月中旬にJARE-43の「しらせ」が立ち寄ることになっている。本研究小集会では, これら複数船による時系列観測のコアメジャメントとなっている, 1) 一次生産, 2) ガス生産過程, 3) 生態系変動, 4) フラックス研究の4課題に関連した研究課題の検討が行われた。また, 乗船候補者の確認, 「専用観測船」に必要な諸設備の検討が行われた。 A workshop on "Planning of Future Science in the Antarctic Ocean Study with Cooperation among Study Groups" was held on 19-21 May 2001,at the Ohishi Seminar House, National Institute of Polar Research, with 20 participants. It had been decided that the 43rd Japanese Antarctic Research Expedition (JARE-43) will charter a research vessel other than "Shirase" to conduct oceanographic studies in the Antarctic Ocean in February 2002. This project is the first attempt for JARE, which has been conducted for more than 40 years. The "Aurora Australis", Australian National Antarctic Research Expedition, and the "Hakuho Maru", Ocean Research Institute, University of Tokyo, plan research cruises in the same sea area as the JARE charter ship, in November-December 2001 and January 2002,respectively. "Shirase" will visit the similar area in March 2002. Consequently, time serial observations will be possible using these vessels. In this workshop, science plans for the core measurements, that is, 1) primary production, 2) gas production process, 3) variation of ecosystems and 4) flux study, were discussed. Moreover, candidates of the participants and the equipments and facilities for the JARE charter ship were discussed. departmental bulletin paper